Comparison of DCE-MRI of murine model cancers with a low dose and high dose of contrast agent. (January 2021) - Zhou, Xueyan; Fan, Xiaobing; Mustafi, Devkumar; Pineda, Federico; Markiewicz, Erica; Zamora, Marta; Sheth, Deepa; Olopade, Olufunmilayo I.; Oto, Aytekin; Karczmar, Gregory S.
Highlights: Low dose (LD) dynamic contrast enhanced MRI can be as effective as high dose (HD). There are strong correlations between LD and HD pharmacokinetic parameters. Dynamic range of LD parameters is much greater than that of HD parameters. There were almost no T2* effects for LD on pharmacokinetic parameters. Abstract: There are increasing concerns regarding intracellular accumulation of gadolinium (Gd) after multiple dynamic contrast enhanced (DCE) MRI scans. We investigated whether a low dose (LD) of Gd-based contrast agent is as effective as a high dose (HD) for quantitative analysis of DCE-MRI data, and evaluated the use of a split dose protocol to obtain new diagnostic parameters. Female C3H mice (n = 6) were injected with mammary carcinoma cells in the hind leg. MRI experiments were performed on 9.4 T scanner. DCE-MRI data were acquired with 1.5 s temporal resolution before and after a LD (0.04 mmol/kg), then again after 30 min followed by a HD (0.2 mmol/kg) bolus injection of Omniscan. The standard Tofts model was used to extract physiological parameters (K trans and ve ) with the arterial input function derived from muscle reference tissue. In addition, an empirical mathematical model was used to characterize maximum contrast agent uptake ( A ), contrast agent uptake rate (α) and washout rate (β and γ). There were moderate to strong correlations (r = 0.69–0.97, p < 0001) for parameters K trans, ve, A, α and β from LD versus HD data. On average, tumor parameters obtained from LD data were significantly larger (p < 0.05) than those from HD data. The parameter ratios, K trans, ve, A and α calculated from the LD data divided by the HD data, were all significantly larger than 1.0 (p < 0.003) for tumor. T2 * changes following contrast agent injection affected parameters calculated from HD data, but this was not the case for LD data. The results suggest that quantitative analysis of LD data may be at least as effective for cancer characterization as quantitative analysis of HD data. In addition, the combination of parameters from two different doses may provide useful diagnostic information.